Reaction mechanism and film properties of the atomic layer deposition of ZrO2 thin films with a heteroleptic CpZr(N(CH3)2)3 precursor - Choi, Ae Rim; Seo, Seunggi; Kim, Seiyon; Kim, Dohee; Ryu, Seung Wook; Lee, Woo Jae; Oh, Il Kwon (Applied Surface Science, 2023)
The surface reaction of a heteroleptic precursor in the atomic layer deposition (ALD) of ZrO2 has been investigated using atomically thin films for scaled-down semiconductor devices. Heteroleptic precursors have been widely used in ALD. Because different ligands in heteroleptic precursors have different reaction pathways, understanding the surface reaction is crucial. In this study, we investigate the growth mechanisms of thin films using a CpZr(N(CH3)2)3 precursor with different reactants, such as H2O and O2 plasma. Chemical composition, surface roughness, film density, and microstructures were analyzed through electron microscopy and X-ray techniques together with quantum chemical calculations to elucidate the ZrO2 growth mechanism. The results showed that the reaction pathway of Zr–Cp ligand exchange with surface hydroxyl groups is less favorable than the Zr–N(CH3)2 reaction pathway. Furthermore, H2O molecules showed less effective oxidation reactions with Cp ligands than with alkyl amide ligands. In contrast, all the ligands were completely removed, resulting in negligible impurity incorporation, as revealed via X-ray photoelectron spectroscopy, when O2 plasma was used, leading to an improved leakage current (30-fold reduction). We believe that these findings on the surface reactions of heteroleptic ALD precursors will be helpful for developing future scaled-down semiconductor devices.
Keywords: Atomic-layer deposition; Cp* ligand; Cpzr(N(CH3)2)3 precursor; Growth mechanisms; Heteroleptic; Heteroleptic precursor; Reaction films; Reaction mechanism; Reaction pathways; Thin-films; Atomic layer deposition; CpZr(N(CH3)2)3 precursor; Heteroleptic precursor; Reaction mechanism; ZrO2